2019
DOI: 10.1093/jxb/erz532
|View full text |Cite
|
Sign up to set email alerts
|

Molecular bases of responses to abiotic stress in trees

Abstract: Trees are constantly exposed to climate fluctuations, which vary with both time and geographic location. Environmental changes that are outside of the physiological favorable range usually negatively affect plant performance and trigger responses to abiotic stress. Long-living trees in particular have evolved a wide spectrum of molecular mechanisms to coordinate growth and development under stressful conditions, thus minimizing fitness costs. The ongoing development of techniques directed at quantifying abioti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
63
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 78 publications
(72 citation statements)
references
References 179 publications
3
63
0
2
Order By: Relevance
“…Transcriptome studies, such as RNA-seq, have been used to explore the complexities of drought stress combined with other environment factors in woody plants ( Estravis-Barcala et al, 2019 ). The advantage of transcriptome study is that it not only unravels the transcriptional regulatory networks under any stress combination but also provides detailed transcriptional events in genotype-, tissue-, and developmental stage-specific bases ( Cohen et al, 2010 ).…”
Section: Complexities and Research Strategies Of Drought Response Inmentioning
confidence: 99%
See 1 more Smart Citation
“…Transcriptome studies, such as RNA-seq, have been used to explore the complexities of drought stress combined with other environment factors in woody plants ( Estravis-Barcala et al, 2019 ). The advantage of transcriptome study is that it not only unravels the transcriptional regulatory networks under any stress combination but also provides detailed transcriptional events in genotype-, tissue-, and developmental stage-specific bases ( Cohen et al, 2010 ).…”
Section: Complexities and Research Strategies Of Drought Response Inmentioning
confidence: 99%
“…Similar to Arabidopsis and rice, woody plant species are also negatively affected by drought, including reduced plant growth, inhibited wood formation, and increased susceptibility to pathogens ( Fernàndez-Martínez et al, 2013 ; Yin et al, 2014 ; Polle et al, 2019 ). With the approaches of genetics and omics, studies on response of woody plants have identified many important TFs, and the transcriptional regulation of drought response is emerging ( Estravis-Barcala et al, 2019 ). In this review, we will provide an update on the recent progress of the role of TFs in drought response in the model plant, Arabidopsis , and highlight findings in the woody genus, Populus .…”
Section: Introductionmentioning
confidence: 99%
“…Imminent effects of climate change will, in many areas, result in rapid increases in temperatures, drought, and extreme weather (Li, 2015). The sessile habit and longevity of tree species mean they must have sufficient phenotypic plasticity to tolerate the wide range of environmental conditions that occur during their lifespans (Estravis‐Barcala, 2019). Similarly, trees are potentially more vulnerable than other plants under changing climate scenarios as they have long generation times, with the persistence of a particular tree species dependent on adaptive capacity to stress, plasticity, and migration potential (Aitken, Yeaman, Holliday, Wang, & Curtis‐McLane, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Although knowledge of the ability of tree species to tolerate environmental stresses is essential for our understanding of how trees will respond to the effects of climate change (Estravis‐Barcala, 2019), we lack data on the stress tolerance of specific taxa (Chaves, 2002). Water availability varies spatially and temporally and has also been found to be an important determinant of functional traits in trees (Terra, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation